Analisis Kelayakan dan Faktor-Faktor yang Mempengaruhi Usahatani Padi di Desa Ngasin Kecamatan Balongpanggang Kabupaten Gresik: Feasibility Analysis and Factors Influencing Rice Farming in Ngasin Village, Balongpanggang District, Gresik Regency - Widodo, Pramudya Wisnu; Dianto, Andri Krisna (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This research was conducted deliberately to determine the feasibility and factors that influence rice farming, especially in Ngasin Village, Balongpanggang District, Gresik Regency, which is a rice-producing village that has the largest rice planting area (rice fields) in Balongpanggang District, Gresik Regency, East Java Province. and To find out the factors that affect rice farming in the region. This study used a quantitative approach with a population and research sample using 60 respondents from farming residents in Ngasin Village, Balongpanggang District, Gresik Regency. The data analysis method in this study uses Regression Ordinary Least Square (OLS) with SPSS Software. SPSS software is one of the Regression completion procedures that has a high degree of flexibility in research that links theory and data that can be carried out on variables in research. The results of the analysis show that partially the variables of land, seed, fertilizer, labour, business experience have an effect on agricultural output and simultaneously all variables have an effect on agricultural output. The fertilizer factor has the most significant effect with a value of 0.001 <0.05. Analysis of the R/C ratio obtained a result of 4.72 based on the eligibility criteria for rice farming with an R/C calculation > 1, so rice farming in the study area was said to be feasible and profitable.